Motion Graphic pada Video Dokumenter tentang Bendungan Pasar Baru di Tangerang - Haidar, Naufal Umar; Lucius, Christophera Ratnasari (Fakultas Desain Universitas Komputer Indonesia, 2025)
The Pasar Baru Dam has maintained the survival of Tangerang City for a long time. Since the establishment of this building during the Dutch colonial period, this dam has provided many benefits. The Pasar Baru Dam documentary video is a documentary video that discusses the Pasar Baru Dam in Tangerang City. This video contains various kinds of information about the dam. The purpose of this design is to examine a Motion Graphic design that is used to support data and information through visual media which is applied to the Pasar Baru Dam documentary video. The research method used in this design is qualitative, which includes data collection methods in the form of interviews, observation and literature study. The results obtained from this design are in the form of Motion Graphics which present information about the Pasar Baru Dam as supporting media in the documentary video about the Pasar Baru Dam.